Variability and predictability of elite competitive slalom canoe-kayak performance - Nibali, M.; Hopkins, W. G.; Drinkwater, E. (European Journal of Sport Science, 2011)
Little is known about the race performance characteristics of elite-level slalom canoeists or the magnitude of improvement necessary to enhance medal-winning prospects. Final placing in this sport is determined by the aggregate of semi-final and final run times inclusive of penalty times. We therefore used mixed linear modelling to analyse these times for finalists ranked in the top and bottom half in the men's canoe, men's kayak, and women's kayak boat classes at World Cups, World Championships, and Olympic Games from 2000 to 2007. The run-to-run variability for top-ranked athletes at different courses ranged from 0.8% to 3.2% (90% confidence limits /1.11-1.31), reflecting differences in how challenging these courses were. The race-to-race variability of aggregate run time was 1.2-2.1% (/~1.09); 0.3 of this variability yields the smallest worthwhile enhancement of 0.4-0.6%. The variabilities of bottom-ranked finalists were approximately double those of top-ranked finalists. The home advantage was small (0.3-0.8%), and incurring a penalty had a marginal effect on reducing actual run time (0.2-0.7%). Correlation coefficients for performance predictability within competitions (0.06-0.35), within years (0.12-0.47), and between years (0.12-0.43) were poor. In conclusion, the variability of performance and smallest worthwhile enhancements in slalom canoe-kayaking are larger than those of comparable sports, and race outcomes are largely unpredictable.